2010
DOI: 10.1002/eqe.1064
|View full text |Cite
|
Sign up to set email alerts
|

The applicability of the N2 method to the estimation of torsional effects in asymmetric base‐isolated buildings

Abstract: The paper deals with the applicability of the extended N2 method to base-isolated plan-asymmetric building structures. The results obtained by the usual pushover analysis of a 3D structural model are further combined with the aid of linear dynamic (spectral) analysis to account for the dynamic effects caused by structural asymmetry. In the paper, the method has been applied to the seismic analysis of a mass-eccentric four-storeyed RC frame building isolated with lead rubber bearings. Three different positions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Because it provides accurate estimates for the target displacement of equivalent SDOF models, it can also be used for the determination of target displacements when using extended pushover‐based methods (e.g. ), which approximately take into account higher mode effects in elevation or, for example, extend the applicability of the pushover‐based method for seismic performance assessment of base‐isolated buildings.…”
Section: Discussionmentioning
confidence: 99%
“…Because it provides accurate estimates for the target displacement of equivalent SDOF models, it can also be used for the determination of target displacements when using extended pushover‐based methods (e.g. ), which approximately take into account higher mode effects in elevation or, for example, extend the applicability of the pushover‐based method for seismic performance assessment of base‐isolated buildings.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the response of the superstructure may be substantially improved if the isolation system is torsionally flexible and if the center of stiffness of the isolated base lies in the vicinity of the (average) center of stiffness of the superstructure. Koren 2008 andKilar 2011 present and discuss the application of the N2 method to a one-way eccentric base isolated building. Comparisons of results with the average results of nonlinear dynamic analyses showed that the extended N2 method could, with certain limitations, provide a reasonable prediction of the torsional influences in minor to moderately asymmetric base-isolated structures.…”
Section: Base Isolationmentioning
confidence: 99%
“…It is protected by a patent that has been filed at the Slovenian Intellectual Property Office (SIPO). The principle of the solution is analogous to that of sliding seismic base isolation systems [39][40][41][42][43][44][45][46][47].…”
Section: Description Of the Proposed Foundation Systemmentioning
confidence: 99%